Topical dermocosmetics and acne vulgaris. Issue 1 (15th November 2020) - Conforti, Claudio; Giuffrida, Roberta; Fadda, Sara; Fai, Annatonia; Romita, Paolo; Zalaudek, Iris; Dianzani, Caterina
Abstract: Acne is a highly common skin disease especially among teenagers. Modern acne treatments are based also on the use of moisturizers, cleansers and sunscreens. In choosing the right cleanser, it is important to consider some aspects: the interaction between skin type and the cleanser, the optimal time and method of cleaning and the cosmetic perception of the patient. The aim of our review is to highlight the importance of choosing the most suitable topical dermocosmetics for the different skin types, as well as the most effective timing and method to combine dermocosmetics with the standard acne treatment. A search in literature for selected key words was performed using PubMed. Additional papers were identified based on author expertise. Treatment of acne patients should include education for proper daily skin hygiene, including protection from environmental damage. However, given the low number of clinical studies on cleansers, it is difficult to make reliable recommendations. The correct choice and use of topical dermocosmetics are fundamental in the management of acne patients. Daily use of moisturizers, cleansers and sunscreens can reduce both inflammatory and non‐inflammatory acne lesion counts and may be helpful for acne treatment if combined with specific drugs.